A new species of the family Theaceae from central VietNam - Truong, Luu Hong; Gioi, Tran; Dat, Nguyen Quoc; Cuong, Nguyen Hieu (Academia Journal of Biology, 2018)
Camellia yenhoae (Theaceae) is described as a new species of section Piquetia from Hon Ba Nature Reserve, Khanh Hoa province, Central Vietnam. The new taxon is close to C. piquetiana, but differs from the later by having ovate, slightly longitudinally striated and 3‒4-locular ovaries and 3‒4 styles connate at basal 1/5‒1/3 part and glabrous on apical 1/4 part. A key to all known species of the section is given.